Tanggung Jawab Penerima Protokol terhadap Gugatan atas Akta yang Dibuat Oleh Pemberi Protokol - Winda Sari; Yetniwati Yetniwati; M. Zulfa Aulia (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the responsibility of notaries who receive notary protocols in relation to lawsuits concerning deeds made by the protocol-giving notary, as well as the form of legal protection available to the receiving notary. This topic is important because, in judicial practice, notaries who merely receive and store notary protocols are often involved as defendants or co-defendants in civil disputes over deeds they did not create, which results in legal uncertainty regarding the limits of notarial responsibility. This research uses a normative juridical method with statutory, conceptual, and case approaches. The statutory approach analyzes provisions of the Notary Law governing authority, responsibility, and protocol transfer, while the conceptual approach refers to theories of legal responsibility and legal protection. The case approach examines court decisions involving notaries receiving protocols in disputes over notarial deeds. The results show that a notary receiving a protocol is not responsible for legal problems arising from the substance of the deed, as responsibility remains with the notary who drafted it. The receiving notary only bears administrative responsibility, limited to storing, maintaining, and providing access to the protocol in accordance with statutory provisions. Furthermore, legal protection for notaries receiving protocols is primarily repressive in nature through the right of refusal as stipulated in Article 16 paragraph (1) letter f of the Notary Law. This study contributes to notarial law literature by clarifying the boundary between administrative and substantive responsibility and reinforcing consistent judicial application of Article 65 of the Notary Law.